EFFECT OF EARLY MOBILIZATION IN PEDIATRIC PATIENT AFTER ATRIAL SEPTAL DEFECT CLOSURE: A CASE STUDY - Jayanti, Fitri Dwi; Rahayu, Umi Budi; Setiawan, Purnomo Gani (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Congenital Heart Disease (CHD) is a congenital disease since the child was born due to the formation of a less than perfect heart. Atrial Septal Defect (ASD) is one of the common CHD. ASD occurs because the partition separating the right and left atriums is damaged, which causes blood rich in oxygen and carbon dioxide mixed. Valve repair surgery in ASD is recomendation and safe treatment procedure with low mortality rate. Bed rest after surgery can lead to prolonged immobilization according to the recovery period of each individual. The usual treatment for physiotherapy is early mobilization to reduce the disorder.Case Presentation: A 6-year-old child was referred to RSUP Semarang with complaints of discomfort and dyspnea during activities. In December 2019 the family took the child to one of the doctors in Salatiga, and the doctor diagnosed that the child had congenital heart disease and was advised to have an examination. The results of catheterization and echocardio examination showed that the child had ASD II.Management and Outcome: Treatments provided such as mobility in bed, range of motion (ROM) exercises, transfers, ambulation and walking exercises. The measuring instrument used is 6 Minute Walk Test (6MWT) which is done when the patient is able to walk and use how long the patient stays in the hospital.Discussion: Early mobilization following surgery in Intensive Care Unit (ICU) is effective to prevent the risk of bed rest and prolonged stay in ICU as well as prevent deep vein thrombosis, pneumonia, preasure ulcers (decubitus) and can improve functional mobility. An important element for the recovery of patients post-cardiac surgery, is not the type of early mobilization but rather interventions that start from the best time according to the patient's condition to prevent the harmful effects of a long bed rest.Conclusion : Early mobilization given postoperatively can prevent the risk of worsening due to long bed rest, long stay in the hospital and can improve functional mobility. Early mobilization and breathing exercise can produce positive effects for patients post cardiac surgery.